How the structure of a medium is seen by an acoustic wave - MAŁECKI, Ignacy (Archives of Acoustics, 1979)
Division of heterogeneous media into three types, depending on the dimensions of heterogeneities. Media with macroheterogeneities occurring naturally and in technological materials. Chraracterization of microheterogeneities. Frequency and energy transport ranges requiring quantum representation of waves in media with heterogeneities caused by crystal structure defects. Quantum phenomena and background noise for audible sounds. Density of phonons occurring in acoustic impulses. Quantum phenomena possible in biological substances.